Mutual learning on key policy issues in food systems transformation between Africa and China - CGIAR Initiative on National Policies and Strategies (CGIAR System Organization, 2023)
Academy of Global Food Economics and Policy of China Agricultural Institute in collaboration with IFPRI-ESSP and CGIAR Initiation on National Policies and Strategies (NPS) organized a half-day Roundtable Dialogue on “Mutual learning on key policy issues in food systems transformation between Africa and China” on May 17, 2023 at ILRI Campus, Addis Ababa, Ethiopia. High level delegates from China Agricultural University, ILRI Board of Trustees, Government Universities, African Union and Policy Study Institute, Ethiopian Agricultural Transformation Institute participated in the discussion.